Perceived stigma, discrimination and psychological problems among patients with epilepsy - Malik, Najma Iqbal; Fatima, Rabia; Ullah, Irfan; Atta, Mohsin; Awan, Ashraf; Nashwan, Abdulqadir J.; Ahmed, Saeed (Frontiers in Psychiatry, 2022)
Objective The current study sought to investigate the effects of perceived stigma and discrimination on epilepsy patients' psychological problems, such as depression, anxiety, and quality of life. Study design A purposive sampling technique was used in this cross-sectional study. Materials and methods The sample consisted of 186 patients with epilepsy. The Stigma Scale, Depression Anxiety Stress Scale, and Quality of life in Epilepsy-10 were used to measure the study variables. Results Findings showed that both the perception of stigma and discrimination have a significant positive correlation with depression as well as anxiety. Stigma is a significant positive predictor of depression and anxiety at [F (1, 184) = 27.8, 15.92, p < 0.001, 0.001, respectively] and explains 12.7 and 7.5% variance that could be attributed to Stigma. Stigma is also a significant predictor of quality of life at [F (1, 184) = 16.10, p < 0.001] and explains the 7.5% variance that could be attributed to Stigma. Results also indicate that discrimination is a significant positive predictor of depression and anxiety at [F (1, 184) = 32.39, 19.91, p < 0.001] and explains 15 and 9.8 % variance, respectively, that could be attributed to Stigma. However, stigma negatively predicts quality of life at [F (1, 184) = 20.34, p < 0.001] and explains 10 % variance. Non-significant differences were found in all the demographic variables (i.e., gender, socio-economic status, and disease duration), except the quality of life was significantly high among individuals with high Socio-economic status. Conclusions Stigma is significantly higher in epileptic patients and has a detrimental effect on the patient's quality of life, recovery, and prognosis. Thus, there is undoubtedly a need to address psychological issues, most notably the stigma associated with illnesses. Psychologists, psychiatrists, other physicians, and care givers of epileptic patients must pay close attention to the stigma in this patient population.